Role of DHA in a Physicochemical Study of a Model Membrane of Grey Matter - Cuenca, Victor E. (2024)
The present study investigates a multicomponent lipid system that simulates the neuronalgrey matter membrane, employing molecular acoustics as a precise, straightforward, andcost-effective methodology. Given the significance of omega-3 polyunsaturated fatty acids in thefunctionality of cellular membranes, this research examines the effects of reducing 1-palmitoyl-2-docosahexaenoylphosphatylcholine (PDPC) content on the compressibility and elasticity of theproposed membrane under physiological conditions. Our results align with bibliographic data obtainedthrough other techniques, showing that as the proportion of PDPC increases in the grey mattermembrane model, the system’s compressibility decreases, and the membrane’s elasticity increases, asevidenced by the reduction in the bulk modulus. These results could be interpreted in light of theemerging model of lipid rafts, in which esterified DHA infiltrates and remodels their architecture.We contend that the results obtained may serve as a bridge between biophysics and cellular biology.